Aktualitas al-Qur'an dan Problematika Makna dalam Bahasa Arab - Pathollah, Akhmad Ghasi (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2020)
Exactly, all the prosess of linguistic activity such as morfology, sintaxis, stylistic and the others, will oriented to get and explore the meanings behind the text. And al-Qur’an as one of the sacred texts should be explored all aspects of it’s meanings. In this context, Arabic Language as the main instrument used in al-Qur’an have to breaked down from it’s basic contruction until it’s complemented contruction. In the other side, simbolity or textuality inside the language save several meanings as the potention to be actual on reader either on mind as understanding or practically of it. Therefore, this reasearch will explore the actuality of al-Qur’an and it’s relation with several meanings behind the text. The problem is existence of more from one meaning behind the text either word or sentence until paragraph and wacana. So, the existence of Semantic as a comprehensive prosess in linguistic activity is realistic conclusion. And the conclusion of this is to confirm problem of exsistence more one meanings behind Arab Language text and its connection with the al-Qur’an and it’s actuality